The Relationship Of Leadership Style, Communication, And Work Discipline To The Performance Of Employees PT. Telekomunikasi Indonesia - Siti Megawati Dahlan; Muhammad Ridwan Basalamah; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract PT Telkom Indonesia (Persero) Tbk is a State-Owned Enterprise (BUMN) engaged in telecommunications services with the primary function and goal of increasing access to adequate communication for the community. This study aims to determine the effect of Leadership Style—communication and work discipline- on PT Telkom employees' performance. The sample used in this study was 42 employees. This study uses a quantitative approach method. This study's data used a Likert scale questionnaire using the multiple linear analysis methods with the help of SPSS software. The results show that leadership style, communication, and work discipline simultaneously have a significant effect on employee performance, leadership style partially has a significant effect on employee performance, communication partially has a significant effect on employee performance, work discipline partially has a significant effect on employee performance. Keywords: Leadership Style, Communication, Work Discipline, and Employee Performance